GE_GERICHTE P/13209/2018 vom 15. Januar 2019 - GE Cour de justice (2019)
AUTORITÉ DOUANIÈRE; TRIBUNAL PÉNAL; COMPÉTENCE; AMENDE; CONVERSION DE LA PEINE | DPA.10.letc; LaCP.50; CPP.363.al3; LaCP.41; LaCP.42